The Unexpected Helical Supramolecular Assembly of a Simple Achiral Acetamide Tecton Generates Selective Water Channels. Issue 33 (5th May 2022) - Dumitrescu, Dan G.; Rull‐Barull, Jordi; Martin, Anthony R.; Masquelez, Nathalie; Polentarutti, Maurizio; Heroux, Annie; Demitri, Nicola; Bais, Giorgio; Moraru, Ionut‐Tudor; Poteau, Romuald; Amblard, Muriel; Krajnc, Andraž; et al.
Abstract: Achiral 2‐hydroxy‐ N ‐(diphenylmethyl)acetamide (HNDPA) crystallizes in the P 61 chiral space group as a hydrate, building up permeable chiral crystalline helical water channels. The crystallization‐driven chiral self‐resolution process is highly robust, with the same air‐stable crystalline form readily obtained under a variety of conditions. Interestingly, the HNDPA supramolecular helix inner pore is filled by a helical water wire. The whole edifice is mainly stabilized by robust hydrogen bonds involving the HNDPA amide bonds and CH … π interactions between the HNDPA phenyl groups. The crystalline structure shows breathing behavior, with completely reversible release and re‐uptake of water inside the chiral channel under ambient conditions. Importantly, the HNDPA channel is able to transport water very efficiently and selectively under biomimetic conditions. With a permeability per channel of 3.3 million water molecules per second in large unilamellar vesicles (LUV) and total selectivity against NaCl, the HNDPA channel is a very promising functional nanomaterial for future applications. Abstract : Water wire transfer : A simple achiral hydrated acetamide self‐organizes into a chiral channel with highly mobile water molecules. The crystalline architecture displays breathing behavior near room temperature with fully reversible release and re‐uptake of water molecules. The water transport is very efficient compared to that with previously reported artificial water channels and has a very good selectivity against NaCl; it could therefore be an efficient candidate for desalination processes.